1969
DOI: 10.1111/j.1365-2621.1969.tb10358.x
|View full text |Cite
|
Sign up to set email alerts
|

The Volatile Components of Irradiated Beef and Pork Fats

Abstract: SUMMARY Samples of beef and pork fats were irradiated under vacuum at seven doses ranging from 0.5 to 6.0 megarads. Of the components produced by irradiation, 41 were identified by gas chromatography and mass spectrometry. These include a series of n‐alkanes, 1‐alkenes, internally unsaturated alkenes and alkadienes. The latter two groups of compounds have not been reported previously in meats or meat fats. In addition, hexadecanal, octadecanal and octadecenal were found to be produced in relatively large quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…Since Nawar's group (2)(3)(4) reported that some hydrocarbons are exclusively produced by γ-radiation of lipids and lipid-containing foods, hydrocarbons have been extensively studied as a marker to detect irradiation of foods (5)(6)(7)(8)(9). Two types of hydrocarbons are predominantly produced by irradiation of fatty acids in lipids: one has one carbon less than the parent fatty acid (n-1), and the other has two carbons less and an additional double bond at position 1 (n-2, 1-ene) (10).…”
mentioning
confidence: 99%
“…Since Nawar's group (2)(3)(4) reported that some hydrocarbons are exclusively produced by γ-radiation of lipids and lipid-containing foods, hydrocarbons have been extensively studied as a marker to detect irradiation of foods (5)(6)(7)(8)(9). Two types of hydrocarbons are predominantly produced by irradiation of fatty acids in lipids: one has one carbon less than the parent fatty acid (n-1), and the other has two carbons less and an additional double bond at position 1 (n-2, 1-ene) (10).…”
mentioning
confidence: 99%
“…Gamma radiation treatments caused a loss of tocopherols in the peanut oil extracted (Bhatti et al, 2010). Since Nawar's group (Champagne and Nawar, 1969;Dubravcic and Nawar, 1969) reported that some hydrocarbons are exclusively produced by the γ-radiation of lipids and lipid-containing foods, hydrocarbons have been extensively studied as markers to detect the irradiation of foods. Two types of hydrocarbons are predominantly produced by the irradiation of fatty acids: a hydrocarbon that has one carbon less than the parent fatty acid (C n -1 ) and a hydrocarbon that has two carbons less and an additional double bond at position 1 (C n -2 , 1-ene) (Dubravcic and Nawar, 1968;Spiegelb erg et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…2-TeCB has also been found in irradiated chicken meat, papaya, and mango Stewart et al, 2000). Some of 2-ACBs are reported as carcinogenic properties (Delincée and Pool-Zobel, 1998) and hydrocarbons influence the flavor of meat products (Champaign and Nawar, 1969). Raul et al (2002) reported that Wistar rats received 3.2 mg/kg body weight of 2-tetradecylcyclobutanone (2-TCB) or 2-(5'-tetradecenyl) cyclobutanone (2-TeCB) daily for 6 months developed tumors in the colon.…”
Section: Radiation-induced 2-alkylcyclobutanonesmentioning
confidence: 99%